How IT can enhance professional practice with regards to smart-phones and social networks? - Hassan, Nuradin Ibrahim; Hussain, Mohammad Khalid; Ibrahim, Jamaludin (International Journal of Management and Commerce Innovations, 2016)
The main objective of the paper is to link, how smart-phones and social media can enable or enhance professional practice in general. This is helps in understanding how these technologies help IT consultants within the realm of their organizations with regard to their daily activities as well as marketing. Most organizations need IT to optimize their organization services that they offering to their customers. The paper also discusses how these technologies can be used to engage with the customer segment.